IMPACT OF LANGUAGE BARRIERS ON TEACHING RETURNEE STUDENTS: SCHOOL TEACHERS’ VIEWS AND STRATEGIES - Abat, Diana (Nazarbayev University Graduate School of Education, 2022)
Over one million ethnic Kazakhs have returned to their homeland and received the status of “returnee” since 1991 (Ministry of Labour and Social Protection of Population, 2020). However, many of the returnees of school age face language barriers and differences in educational systems that bring discomfort to integrating into the Kazakhstani mainstream schools. This qualitative study uses the concept of funds of knowledge (Moll et al., 1992) to understand and explain the views about the language barriers teachers face while teaching returnee students and the impact of these language barriers on teaching practices through the following research questions: (1) What are mainstream schoolteachers’ views about the language barriers they face while educating returnee students?; (2) How do these language barriers as viewed by teachers impact their teaching practices?; and (3) What strategies do teachers use to cope with these language barriers? The participants of the study were ten mainstream secondary school teachers. The participants had various teaching experiences with returnee students, subjects being taught, and the country of origin of returnee students. The semi-structured interviews conducted among the participants consisted of 15 questions to elicit language barriers, their impact on teaching practices, and strategies to cope with them. The study results demonstrate that teachers view the barriers they face with returnee students lie in their language proficiencies. Furthermore, the impact of these barriers was twofold: some teachers viewed returnee students’ funds of knowledge as a positive stance and others negative one. Lastly, teachers’ strategies show how seriously teachers work to alleviate the language barriers. The study presented implications for teacher trainers, school administrators, and think tanks to support teachers while teaching returnee students.
Keywords: Type of access: Embargo